THE EFFECTS OF CERTAIN GASOTRANSMITTERS INHIBITION ON HOMOCYSTEINE ACUTELY INDUCED CHANGES ON RAT CARDIAC ACETYLCHOLINESTERASE ACTIVITY - Djuric, Dragan M (Scripta Medica, 2019)
Background: Hyperhomocysteinemia is linked to higher level of acetylcholinesterase (AChE) in brain, but there is lack of data referring to influence of homocysteine (Hcy) on cardiac AChE and the role of gasotransmitters in these effects. Therefore, this study aim was to assess the role of gasotransmitter inhibitors in Hcy-induced changes on rat cardiac AChE activity. Material and Methods: Study involved 72 male Wistar albino rats divided into 6 groups: 1) Control group – saline (1ml 0.9 % NaCl i.p.,); 2) DL-Hcy (8 mmol/kg i.p. DL homocysteine (DL-Hcy)); 3) L-NAME (10 mg/kg i.p. Nω-Nitro-L-arginine methyl ester (L-NAME), inhibitor of NO production); 4) DL-PAG (50 mg//kg i.p. DL-propargylglycine (DL-PAG), inhibitor of H2S production); 5) DL-Hcy+L-NAME (8 mmol/kg i.p. DL-Hcy + 10 mg/kg i.p. L-NAME); and 6) DL-Hcy+DL-PAG (8 mmol/kg i.p. DL-Hcy + 50 mg//kg i.p. DL-PAG). In all experimental groups, tested substances were administered in a single dose, intraperitoneally, 60 minutes before animals’ euthanasia. AChE activity was measured in the rats’ cardiac tissue homogenate. Results: Administration of Hcy and L-NAME induced significant decrease in AChE activity compared with control condition. Administration of DL-PAG, DL-Hcy+L-NAME and DL-Hcy+DL-PAG did not induce significant changes in AChE activity compared with control condition. Conclusion: The effects of Hcy on the cardiac AChE activity are in part mediated via interaction with gasotransmitters.